2021
DOI: 10.3390/polym13111882
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Impregnation Technique on the Release of Esomeprazole from Various Bioaerogels

Abstract: The presented study shows the possibility of using bioaerogels, namely neat alginate, pectin, chitosan aerogels, and alginate and pectin aerogels coated with chitosan, as drug delivery systems for esomeprazole. Two different techniques were used for the impregnation of esomeprazole: Supercritical impregnation, and diffusion via ethanol during the sol-gel synthesis. The prepared samples were characterized by employing N2 adsorption-desorption analysis, TGA/DSC, and FTIR. The achieved loadings were satisfactory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Optimizing the drug release kinetics controlled by the diffusion mechanism and polymer degradation for a particular application is very important. Successful attempts have already been made to achieve the controlled release of AIs from biodegradable aerogels in simulated gastric and intestinal fluids [100,101]. In addition, the solubility of AIs with a hydrophobic character was significantly improved by their incorporation into aerogels [94,97,102].…”
Section: Sc Drying For the Preparation Of Aerogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimizing the drug release kinetics controlled by the diffusion mechanism and polymer degradation for a particular application is very important. Successful attempts have already been made to achieve the controlled release of AIs from biodegradable aerogels in simulated gastric and intestinal fluids [100,101]. In addition, the solubility of AIs with a hydrophobic character was significantly improved by their incorporation into aerogels [94,97,102].…”
Section: Sc Drying For the Preparation Of Aerogelsmentioning
confidence: 99%
“…Many studies have confirmed that embedding the AI in biodegradable polysaccharide aerogels is promising for oral drug delivery. Compared to crystalline AIs, these aerogels achieve more controlled release over a period of several hours to several days of testing [100,102,142]. Compared to the incorporation of AIs into aerogels, SC foaming often achieves long-term release of several days to 1-2 months due to the structural properties of polymer foams (PCL, PLA, PLGA), which is why their application is often focused on biomedical purposes (implant coatings, tissue engineering) [118,143].…”
Section: Drug Delivery From Formulations Prepared By Scf Technologiesmentioning
confidence: 99%
“…Esomeprazole has low water solubility and high permeability [ 29 ]. It has better pharmacokinetic (PK) profiling than omeprazole in the management of acid-related problems [ 30 ]. It has been studied that developed hydrogel preparations could be suitable carriers for the delivery of esomeprazole for the improvement of bioavailability [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…EZL is low water-soluble and highly permeable [2]. It has superior pharmacokinetic profiling over omeprazole in monitoring acid-related ailments [3]. The fact that the stability of esomeprazole decreases with a decrease in pH of media means that the contact of EZL with the acidic content of the stomach leads to degradation of EZL and may reduce the bioavailability [4].…”
Section: Introductionmentioning
confidence: 99%